Mesenchymal stem cells from iPS cells facilitate periodontal regeneration - Hynes, K; Menicanin, D; Han, J; Marino, V; Mrozik, K; Gronthos, S; Bartold, P M (Journal of dental research, 2013)
Mesenchymal stem cells (MSC) have been considered as a potential therapy for the treatment of periodontal defects arising from periodontitis. However, issues surrounding their accessibility and proliferation in culture significantly limit their ability to be used as a mainstream treatment approach. It is therefore important that alternative, easily accessible, and safe populations of stem cells be identified. Controlled induction of induced pluripotent stem cells (iPSC) into MSC-like cells is emerging as an attractive source for obtaining large populations of stem cells for regenerative medicine. We have successfully induced iPSC to differentiate into MSC-like cells. The MSC-like cells generated satisfied the International Society of Cellular Therapy's minimal criteria for defining multipotent MSC, since they had plastic adherent properties, expressed key MSC-associated markers, and had the capacity to undergo tri-lineage differentiation. Importantly, the resulting iPSC-MSC-like cells also had the capacity, when implanted into periodontal defects, to significantly increase the amount of regeneration and newly formed mineralized tissue present. Our results demonstrate, for the first time, that MSC derived from iPSC have the capacity to aid periodontal regeneration and are a promising source of readily accessible stem cells for use in the clinical treatment of periodontitis.